Self-Reported Adverse Events of COVID-19 Vaccines in Polish Healthcare Workers and Medical Students. Cross-Sectional Study and Pooled Analysis of CoVaST Project Results in Central Europe - Dziedzic, Arkadiusz; Riad, Abanoub; Attia, Sameh; Klugar, Miloslav; Tanasiewicz, Marta (Journal of clinical medicine, 2021)
BACKGROUND: Optimization of COVID-19 vaccination rate among healthcare personnel is of utmost priority to secure provision of uninterrupted care and to protect the most vulnerable patients. This study, as part of the global CoVaST project, aimed to assess the occurrence of short-term adverse events (SRAEs) of two most administered COVID-19 vaccines, mRNA-based (Pfizer-BioNTech and Moderna) and viral vector-based (AstraZeneca) in healthcare sector workers (HWs). METHODS: A cross-sectional survey-based study was carried out for the first time among 317 Polish healthcare sector personnel and medical students using a validated and pre-tested questionnaire. The online questionnaire included 25 pre-tested, validated questions concerning demographic data, medical parameters, COVID-19-related anamneses, and local or systemic reactions (reactogenicity) associated with COVID-19 vaccination. Descriptive statistics, inferential tests and binary logistic regression were performed. RESULTS: Out of the 247 participating HWs, 79.8% were females, and 77.5% received mRNA-based vaccines, while 24.5% received a viral vector-based vaccine. Cumulatively, 78.9% and 60.7% of the participants reported at least one local and one systemic SRAE respectively, following their COVID-19 first or second dose of vaccine. A wide array of SRAEs was observed, while pain at injection site (76.9%) was the most common local SRAE, and fatigue (46.2%), headache (37.7%), muscle pain (31.6%) were the most common systemic SRAEs. The vast proportion of local (35.2%) and systemic (44.8%) SRAEs subsided up to 1 day after inoculation with both types of vaccines. The mRNA-based vaccine versions seem to cause higher prevalence of local SRAEs, mainly pain within injection site (81.3% vs. 71.7%; p = 0.435), while the viral vector-based vaccine was linked with increased incidents of mild systemic side effects (76.7% vs. 55.3%; p = 0.004) after both doses. Pooled analysis revealed uniform results while comparing the prevalence of SRAEs in HWs as recipients in four central European countries (OR = 2.38; 95% CI = 2.03-2.79). CONCLUSIONS: The study confirmed the safety of commonly administered vaccines against COVID-19, which were associated with mild, self-resolving adverse events. No major vaccine-related incidents were reported which would affect every day functioning, significantly. The younger age group (below 29 y.o.) were associated with an increased risk of adverse events generally. The results enhanced current data regarding COVID-19 vaccination active surveillance in selected occupational groups.
Keywords: vector vaccine; COVID-19; pooled analysis; adverse effects; cross-sectional study; BTN162 mRNA vaccine; healthcare workers; Poland; adverse reactions; prevalence